EFFECT OF HEAT TREATMENT ON CORROSION RESISTANCE OF ALSI10MG ALLOY FABRICATED USING SELECTIVE LASER MELTING IN KOH SOLUTION - Kanigara Kasiyanto, Mahesa
Additive manufacturing (AM) technology has gained growing attention in the past decade due to its potential to produce complex structures or geometries with tight tolerances, cost-effectiveness, and short time-to-market. Aluminum alloy metals are widely utilized in the transportation and electronics industries due to their excellent corrosion resistance in normal atmospheric conditions. However, AlSi10Mg alloys made from AM processes exhibit high surface roughness and thermal residual stress, which could potentially increase susceptibility to corrosion. This research aims to investigate the influence of heat treatment on the microstructure and corrosion resistance of AlSi10Mg alloy obtained through SLM. Corrosion resistance is evaluated through corrosion tests in KOH solutions. Microstructure and specimen morphology are analyzed using Scanning Electron Microscope (SEM) equipped with Energy Dispersive X-ray (EDS). In this study, corrosion tests were conducted using Open Circuit Potential, Cyclic Polarization, Electrochemical Impedance Spectroscopy, and Immersion methods in 0.5 M, 1.5 M, and 2.5 M KOH solutions. Solution treatment and aging heat treatment altered the microstructure of AlSi10Mg alloy from fish scale to an ?-Al matrix with silicon particles, yet did not provide superior corrosion protection than samples fabricated using SLM. OCP results showed improvement in samples’ tendency to corrode after heat treatment. Cyclic results indicate only samples immersed in 0.5 M KOH showed signs of pitting. EIS plotting showed no improvement in passive film resistance after heat treatment. Immersion test showed less mass loss in fabricated samples compared to heat treated by as much as 15-50%